Structure, morphology, and mechanical properties of polysiloxane elastomer composites prepared by in situ polymerization of zinc dimethacrylate - Y. Meng; Y. L. Lu; Z. Wei; L. Q. Zhang (eXPRESS Polymer Letters, 2012)
Methyl vinyl silicone rubber/zinc dimethacrylate (VMQ/ZDMA) composites were prepared through in situ polymerization of ZDMA monomers during the peroxide curing. The polymerization conversion of ZDMA and morphology of the VMQ/ZDMA composites were studied. The results showed that most of the ZDMA monomers participated in the in situ polymerization during the cross-linking of the VMQ matrix and uniform nanophases were formed in the composites. The ‘dissolving-diffusion’ model was used to explain the micro-nano transformation of ZDMA. According to the model, a uniform nano-dispersed structure could be obtained through the in situ reaction even though the initial dispersion of ZDMA in the blends was poor. In addition, tensile tests of VMQ/ZDMA composites showed that ZDMA had a significant reinforcement on the mechanical properties of VMQ, and the best mechanical properties were obtained when the amounts of peroxide and ZDMA were 5 and 40 phr, respectively. The gross crosslink density and ionic crosslink density increased as the amount of ZDMA increased, but the covalent crosslink density decreased slightly. These results indicated that the ionic crosslink structure had a significant effect on the mechanical properties of VMQ/ZDMA composites.